GAI och utmaningar i respekträtten - Om GAI och respekträttsliga intrång - Lam,Isabelle (2025)
Droit au respect is part of the copyright framework’s protection of the au-thor's moral and personal interest in his work. It is regulated by URL para-graph 3, section 2, which reads: A work may not be changed in such a way that the author's literary or artistic reputation or individuality is infringed; nor may the work be made available to the public in such a form or in such a context that is in a stated way offensive to the author. This moral right is currently being challenged by GAI, whose utilisation of protected works during its learning-and-generation processes has given rise to fierce protest from authors whose works have been utilised in these processes. From the authors’ perspective, GAI is contextualised as exploitative, distorting and artistically meaningless. The purpose of this work has thus been to investigate whether these protests may also actualise infringement of the author’s droit a moral. The conclusion of the work is as follows. Only in certain cases will a GAI-model’s learning-and-generation processes take actions which constitute infringements of the author’s droit au respect. The application of URL paragraph 3, section 2 is hindered by the limitation of its prohibited actions to solely the acts of modifying a work or making it available to the public. Only in certain cases do a GAI-models processes act in such a way which fulfils the requirements for the prohibited actions. In most cases, a GAI-model’s processes instead act in such a way to constitute destruction of a work, which is a permitted act under current copyright law.
Keywords: immaterialrätt; EU-rätt; upphovsrätt; respekträtt; GAI